The Complete Pentesting and Privilege Escalation Course - Percival, Rob; Samancioglu, Atil (Packt Publishing, 2021)
Learn and deepen your knowledge in ethical hacking topics such as pentesting and privilege escalation techniques while becoming a certified cyber security professional About This Video Execute privilege escalation for Linux Execute privilege escalation for Windows Solve CTF (Catch the Flag) solutions and move ahead in the game level In Detail We are in an era where cyber security plays an important part and the race between attackers and defenders is tremendously growing. Companies are heavily investing to protect their data. Pentesting and privilege escalation tests prove to be a vital step to eradicate or lower down the vulnerabilities within a system, network, or application to detect weaknesses that an attacker could exploit. Throughout the course, we'll solve a number of vulnerable machines on VulnHub, TryHackMe, and HackTheBox along with the other platforms. The topic of privilege escalation will be thoroughly explained, which provides the best tools to pass a certification such as OSCP. Furthermore, we will not only focus on Linux machines but Windows machines as well. Important topics that will be covered are as follows: Advanced Linux CTF Solutions Linux Privilege Escalation Windows Privilege Escalation Kernel Exploit SUID Sudo Cronjobs Metasploit Potato Attacks BPrute Force Meterpreter Shells Meterpreter Shells By the end of this course, you will have taken a big step to advance your cyber security career. Warning: This course aims to provide a good training for people who want to be cyber security professionals. You should not break the law in any way with the offensive penetration test techniques and you accept the responsibility by taking this course.